Emotional Intelligence: A tool to create Organizational Citizenship Behavior and minimize service sabotage behaviours in the service sector of Pakistan - Younas, Sohail; Mirza, Farhan; Hafeez, Nauman; Ghafoor, Muhammad Mudasar (Pakistan Journal of Humanities and Social Sciences, 2023)
Emotional intelligence helps to predict and control the changing behaviour of employees. Our study focuses on customer service sector employees, organizational citizenship behaviour, and service sabotage. The study also explained the effect of emotional intelligence on OCB with the mediation role of emotional labour. In addition, moderation role of EI between emotional dissonance and service sabotage. The time horizon was longitudinal and descriptive; the geographical area included Gujranwala, Lahore, and Sialkot. The study's findings show a significant positive association of emotional intelligence with organizational citizenship behavior. Emotional intelligence significantly moderates the strength of the relationship between emotional dissonance and service sabotage.